Basis-Anforderungen einer Fachabteilung für Herzchirurgie - Gummert, Jan; Beckmann, Andreas; Bauer, Adrian; Heinemann, Markus; Markewitz, Andreas; Falk, Volkmar; Boening, Andreas (The Thoracic and Cardiovascular Surgeon, 2022)
The evolution and progress in cardiovascular medicine and substantial changes in the German health care system require both a reflection of the principles of patient-centered care in general and an update of the criteria that define a department of cardiac surgery in Germany. This position paper lists the core requirements for a cardiac surgical department with regard to infrastructure, facilities, necessary staff, and standard of care (processes). This standard may be used by hospitals and health care providers to ensure the safety and quality of cardiac surgical departments in Germany.
Keywords: outcomes; quality of life; health economics; quality assurance; cardiac surgery; patient care; heart team